STRATEGIC INTERNAL AUDIT FUNCTIONS AND ORGANISATIONAL OUTCOMES IN DEVELOPING ECONOMIES: EVIDENCE FROM AFRICA AND ASIA (2000–2025) - Drammeh, Lamin K; Leniwati, Driana (Faculty of Economics and Business, 2025)
This study investigates how internal audit functions shape governance, risk management, and organizational performance across six developing economies: The Gambia, Ghana, Kenya, Indonesia, Malaysia, and India between 2000 and 2025. Employing a qualitative comparative case study approach, it analyses secondary data from audit reports, policy papers, and academic sources using thematic analysis. The findings reveal strong audit independence and professional capacity in Kenya and India, contrasted with autonomy and digitalization challenges in The Gambia and Indonesia. Malaysia demonstrates progress through ESG-integrated auditing. The study develops a Cross-Regional Audit Effectiveness Framework linking institutional capacity, digital readiness, and ESG adoption to audit effectiveness. The results show that governance context mediates the strategic impact of internal audit on organizational outcomes. This research fills a gap in cross-regional evidence on how institutional and technological factors jointly determine the strategic role of internal auditing in Africa and Asia.